MALL‐based collaborative writing in second language classroom: A systematic review - Lisha Wang (Future in Educational Research)
AbstractDriven by the affordances and benefits of mobile technology, collaborative writing (CW) supported by mobile technologies has been increasingly implemented in the second language (L2) acquisition context. To shed light on the research foci and provide guidance for future research in this promising area, the present study conducted an in‐depth and systematic review of 25 empirical articles on CW supported by mobile technologies in the L2 context published from 2014 to 2022, including quantitative, qualitative, and mix‐methods research. A holistic analysis of these articles was conducted, covering various aspects such as research themes, research contexts and technology, theoretical/pedagogical frameworks, writing tasks, and instruments. Based on the analysis of the previous research, this study provided pedagogical suggestions concerning writing tasks, group division, participant training, and writing assessment and also explores future research directions.